Circulating miR-29b decrease in response to sarcopenia in patients with cardiovascular risk factors in older Chinese - He, Nana; Zhang, Yuelin; Zhang, Yue; Feng, Beili; Zheng, Zaixing; Ye, Honghua (Frontiers in Cardiovascular Medicine, 2022)
Sarcopenia is a clinical syndrome characterized by a progressive and extensive decline in skeletal muscle mass, muscle strength, and function. Sarcopenia and cardiovascular diseases (CVDs) can coexist, which further decreases the quality of life of patients, and increases the mortality rate. MicroRNAs (miRNAs) are unique posttranscriptional regulators of gene expression whose function in aging-related sarcopenia and CVDs has recently begun to unravel. The aim of the present study is to investigate the relationship between sarcopenia and cardiovascular risk factors (CVRF) in the Chinese elderly and describe the circulating miRNAs in sarcopenia patients with the intention of identifying novel diagnostic and therapeutic tools. The well-established CVRF of diabetes, hypertension, and dyslipidemia were assessed. Multiple logistic regression analyses and linear regressions were used to evaluate the components of CVRF and the number of CVRF in elderly patients with sarcopenia. After adjusting for potential confounders, CVRF was associated with a high prevalence of sarcopenia in elderly Chinese populations. Furthermore, hypertension and dyslipidemia, but not diabetes, were found to be significantly associated with sarcopenia. A linear increase in the prevalence of sarcopenia was found to be associated with the number of CVRF components in the elderly population. Moreover, we used real-time RT-PCR to measure the abundance of the CVDF-related miRNAs in the plasma of a cohort of 93 control and sarcopenia individuals, including miR-29b, miR-181a, and miR-494. We found that plasma miR-29b levels were significantly down-regulated in response to sarcopenia in the elderly with CVDF. In particular, there was a remarkable correlation between miR-29b and ASM/height2. Collectively, knowledge of CVRF, particularly hypertension and dyslipidemia, may help predict the risk of sarcopenia in the elderly. Our data also show that circulating miR-29b can be considered as possible biomarkers for sarcopenia, which may also be used in the CVD assessment of these patients.